A study on the significance of lithology in groundwater quality of Madurai district, Tamil Nadu (India) - Thivya, C.; Chidambaram, S.; Singaraja, C.; Thilagavathi, R.; Prasanna, Mohan Viswanathan; Anandhan, P.; Jainab, I. (Springer, 2013)
The groundwater occurs in hard rock aquifers, which is more predominant in India. It is more common in the southern peninsula especially Tamil Nadu. Madurai district is located in the central part of Tamil Nadu, underlain predominantly by crystalline formations and alluvium along the river course. The study area being a hard rock terrain, the groundwater is stored in cracks, fissures, joints, etc., and hence the quantity is lesser. The frequent failure of monsoon also aggravates the scarcity of this commodity. In this scenario, the quality and hydrogeochemistry of the available quantum of water plays a significant role for the determination of its utility and in tracing out the hydrogeochemical evaluation. Fifty-four groundwater samples were collected representing the entire study area. The samples collected were representative covering all the major litho units of the study area (charnockite -21, fissile hornblende biotite gneiss-21, granite-4, quartzite-3, and 5 samples from flood plain alluvium). The samples collected were analyzed for major ions and were classified for different purposes like drinking, domestic, and agriculture, with respect to lithology.The comparison of the groundwater samples with the drinking water standards shows that few samples fall above the drinking water limit irrespective of lithology. The samples were classified with sodium absorption ratio, electrical conductivity, residual sodium carbonate, sodium percentage (Na %), Kellys ratio, and magnesium hazard, and permeability index for irrigation purpose found that most of the samples were suitable for irrigation purpose irrespective of lithology. Total hardness and corrosivity index were studied for the domestic purpose and found that the samples of the granitic terrain are safe. Apart from this, index of base exchange, Schoellers water type, Stuyfzands classification were attempted along with Gibbs plot to determine the major geochemical activity of the region. The study reveals that the samples collected from granitic and quartzitic terrains are comparatively better for the domestic and drinking purpose due to the presence of resistant minerals to weathering.